in brief - Елена Григорьева; Юлия Никифорова (Проект Байкал)
The brief news presents the events of the second half of the year 2024 in Irkutsk and Siberia, the results of the elections in several organisations of the Siberian Federal District, personal exhibitions and thematic meetings at the Irkutsk House of Architects.